Fintech and financial stability potential influence of FinTech on financial stability, risks and benefits - Milena Vučinić (Journal of Central Banking Theory and Practice, 2020)
Since the last global financial crisis supervisory mechanisms and regulations have become more stringent which have significantly improved resilience of banks therefore positively affecting financial stability. Apart from traditional financial institutions which have been supervised according to strict regulations and standards technological development in financial services commonly called FinTech have introduced new trends providing fast peer to peer lending which directly matches lenders and borrowers thus putting more pressure to policymakers and supervisors. This paper presents potential implications of FinTech developments to financial stability, while explaining FinTech influence to market structure as well as benefits and risks of technologically driven financial innovations to financial stability. The paper stresses out an importance of international cooperation of regulators in order to preserve financial stability in the recent world of technological changes and innovations. FinTech has changed consumers' expectations and preferences while increasing the number of users expecting fast and easily accessible services available on mobile phones and other electronic devices. The paper shows that new technology provides the space for expanding financial services but it also poses additional risks to financial system in terms of microfinancial and macrofinancial risks.
Keywords: F61; F62; E58; E61; E62; G18; G15; F42; F58; 330; financial stability; FinTech; technological developments; financial innovations; market structure